The Rise of a Capital - Bruning, Jelle (Islamic History and Civilization Ser, 2018)
Intro -- ‎Contents -- ‎Acknowledgements -- ‎Transliteration, Dates, and Toponyms -- ‎Abbreviations -- ‎Journals -- ‎Editions of Papyri and Reference Works -- ‎Maps -- ‎Introduction -- ‎1. Studying al-Fusṭāṭ and Its Hinterland -- ‎2. Al-Fusṭāṭ and Political Centrality: A Short Historical Overview -- ‎Chapter 1. The Administrative Relationship between Alexandria and al-Fusṭāṭ -- ‎1. The Establishment of Muslim Rule over Alexandria and the Foundation of al-Fusṭāṭ -- ‎2. Connecting Alexandria to al-Fusṭāṭ 1: The Settlement of Muslim Notables -- ‎3. Connecting Alexandria to al-Fusṭāṭ 2: The Creation of a Military Loyalty Network -- ‎3.1. Alexandria's Muslim Garrison and the Byzantine Capture of 24/645--25/646 -- ‎3.2. Changes at the Top of Alexandria's Civil and Military Administration -- ‎4. Strengthening al-Fusṭāṭ's Control over Alexandria around 40/660: Gubernatorial Presence -- ‎5. Concluding Remarks -- ‎Chapter 2. The Commercial Development of Alexandria after the Foundation of al-Fusṭāṭ -- ‎1. Al-Fusṭāṭ: Commercial Activity in the First/Seventh and Second/Eighth Centuries -- ‎2. Alexandria in Domestic Trade: The Papyrological Evidence -- ‎2.1. The Alexandrian Gold Standard -- ‎3. Alexandria and Interregional Trade -- ‎3.1. The Ceramological Evidence -- ‎3.2. The Literary Evidence: Alexandria on Itineraries -- ‎4. Concluding Remarks -- ‎Chapter 3. Changes in the Military Administration of Upper Egypt and Its Relationship with al-Fusṭāṭ -- ‎1. The Thebaid: The Reach of Muslim Rule before 31/652 and the Establishment of the Southern Frontier near Aswan -- ‎2. The Thebaid: Muslim Authority and the Southern Frontier -- ‎3. Arcadia -- ‎3.1. The Initial Period: 21/641--c. 41/661 -- ‎3.2. Developments after c. 41/661 -- ‎4. Concluding Remarks -- ‎Chapter 4. Al-Fusṭāṭ and the Legal Administration of Upper Egypt.